The effects of Chinese import penetration on firm innovation: Evidence from the Vietnamese manufacturing sector - Duc Anh Dang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper evaluates the impact of Chinese import penetration on the innovation of Vietnamese manufacturing firms from 2011 to 2015, exploiting variations in import exposure by industry specialization and instrumenting for Chinese import penetration using Chinese global exports. Contrary to the existing literature, the paper finds no systematic evidence that rising imports from China make domestic firms adopt new technologies or innovations in their products.
Keywords: L16; O33; F14; 330; China; manufacturing; innovation; trade